2014
DOI: 10.7287/peerj.preprints.254v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swedish high-school pupils’ attitudes towards drugs in relation to drug usage, impulsiveness and other risk factors

Abstract: PrePrintsSwedish high-school pupils' attitudes towards drugs in relation to drug usage, impulsiveness and other risk factors Characteristic were positively related to impulsiveness among drug users. Moreover, although males reported using drugs to a greater extent, but female expressed more positive attitude towards drugs and even reported more impulsiveness than male students. Conclusion:This study reinforces the idea that research must focus on gender differences relative to pro-drug attitudes along with tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…An international comparison between the rates of substance use would show that the students' participated our study had lower liability to substance use as well. In the study carried out by Mousavi et al (2014) in the USA, 4.80% of the pupils indicated using drugs and almost 2.80% of them said that they used drugs regularly (like weekly, monthly, every two months or sometimes). Martin et al (2007) stated that of the young people between the ages of 12 to18 surveyed in Australia, 54% used drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An international comparison between the rates of substance use would show that the students' participated our study had lower liability to substance use as well. In the study carried out by Mousavi et al (2014) in the USA, 4.80% of the pupils indicated using drugs and almost 2.80% of them said that they used drugs regularly (like weekly, monthly, every two months or sometimes). Martin et al (2007) stated that of the young people between the ages of 12 to18 surveyed in Australia, 54% used drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There are findings of the studies suggesting gender as one of the important factors affecting attitudes towards drugs and drug addicts (e.g., Martin et al, 2007;Tekten, 2006;Çırakoğlu and Işın, 2005;Herken et al, 1997). Mousavi et al (2014) counted gender, family, friends and individual characteristics as the factors related with drug use. The results of the study by Tansel (2006) also indicated significant differences between attitudes of students with drug abuse problems depending on students' gender, field of study, parents' educational status, being or not being close to drug containing environment, using or not using substances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations